STUDENTS’ INTERESTS ON INTERNET SECOND LANGUAGE COLLECTIVE VIDEO QUIZZES IN LISTENING NARRATIVE TEXT AT GRADE IX SMP NEGERI 23 MEDAN - Riska Ayunda; Ade Aini Nuran (Universitas Negeri Medan, 2023)
This study aims to analyze and investigate students’ interest to ISL Collective Video Quizzes as interactive media in listening skill of Narrative Text at grade IX SMP Negeri 23 Medan. This research was conducted with Mixed-Method Research. The data were obtained through questionnaire and interview. 28 students were as the source of data to answer 20 questions of the questionnaires related to the students’ interest by Slameto( 2003 ) then to support the data from questionnaire 28 students answer 10 questions from interview and the question also related to the students’ interest. The result of the study showed that the students agreed about they easy to understand the material, enjoy, happy, focus, anthusiast, excited and interest to the subject when the teacher used ISL Collective Video Quizzes on listening narrative text. The types of interest on ISL Collective Video Quizzes from the students’ are Individual Interest, Situatinal Interest, and Topic Interest.The students in the class IX at SMP N 23 Medan have interest on ISL Collective Video Quizzes. There were several indicators of students’ interest according to Slameto (2003) namely are Attention, The Willingness, Needs, Feelings happy or joyful feelings, Teaching Materials and Teachers’Good Attitudes and Participation. From these indicators it’s relate with the reality. Students’ have interest on ISL Collective Video Quizzes because is interesting media for students’ in listening narrative text and can be useful for the students. They can answer the question of the quizz properly and correctly.They also agreed that using ISL Collective Video Quizzes help them in remembering the subject. Moreover, they stated that by using ISL Collective Video Quizzes, they felt more interesting in learning the subject and they did not get bored during the lesson. The researcher concluded that students’ interest on the used of ISL Collective Video Quizzesinin listening to narrative text is positive and usefull for students also can improve their listening skill. Keywords: Students’ Interest, ISL Collective Video Quizzes, Listening Skill, Narrative text